Analysis Of Utilization Of E-Commerce In Dealer Cemara Agung Motor Sumedang - Anggraeni, Anggun; Sudrajat, Arip Rahman (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2024)
The Dealer Cemara Agung Motor Sumedang is a company engaged in the automotive sector, which has suboptimal online sales/transactions caused by several things such as not being given permission by superiors and a lack of human resources in carrying out online sales/transactions. Based on this, this study aims to analyze the use of e-commerce and efforts to increase the use of e-commerce at Dealer Cemara Agung Motor Sumedang. This study uses a qualitative research method approach with the research variable being e-commerce. The sampling technique was carried out by purposive sampling technique. Research informants amounted to 10 people. Research data were analyzed using the Miles and Huberman method with steps including data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate that the use of e-commerce at the Dealer Cemara Agung Motor Sumedang as a whole is not good enough and has not met expectations